MORPHOLOGICAL CHANGES OF THE UTERUS IN EXPERIMENTAL METABOLIC SYNDROME (International Conference on Educational Discoveries and Humanities, 2025)
A high-calorie diet is considered one of the main causes of metabolic syndrome. Most morphologic and physiologic research has focused on morphologic changes in the heart and pancreas. There are especially few studies devoted to morphologic changes in reproductive organs of women in the state of metabolic syndrome. Considering the above, we studied morphologic changes in the uterus and ovaries as an object of study. The results revealed that the main morphologic substrate is changes in the form of destruction and defragmentation in the uterus and ovaries.